2017
DOI: 10.3390/nu9040340
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vitamin D Deficiency Is Associated With Poor Sleep Quality and Night-Time Eating at Mid-Pregnancy in Singapore

Abstract: Plasma 25-hydroxyvitamin D (25OHD) deficiency, poor sleep quality, and night-time eating, have been independently associated with adverse pregnancy outcomes, but their inter-relationships are yet to be evaluated. We aimed to investigate the associations between maternal plasma 25OHD status and sleep quality and circadian eating patterns during pregnancy. Data on pregnant women (n = 890) from a prospective cohort (Growing Up in Singapore Towards healthy Outcomes) were analyzed. Plasma 25OHD concentration was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…As a result, 9 studies were included in our meta-analysis. The detailed study selection is described in Figure 1 [ 20 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, 9 studies were included in our meta-analysis. The detailed study selection is described in Figure 1 [ 20 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in United States [ 20 , 31 ], two in France [ 32 , 34 ], and the rest in other countries. Most studies were mixed gender, two included only women [ 26 , 33 ], and one was only male [ 20 ]. For vitamin D deficiency cut-off value, the included studies mainly used 20 ng/mL [ 20 , 26 , 31 , 33 , 35 ] in accordance with the criteria suggested by Institute of Medicine (IOM) [ 38 ]; three studies used 30 ng/mL [ 32 , 34 , 37 ], and only one study used 10 ng/mL [ 36 ] as the cut-off value.…”
Section: Resultsmentioning
confidence: 99%
“…Of note is that not only constant light, but also diurnal light deficiency and/or continuous darkness, are disruptive for the circadian system. Several conditions related to diurnal light deficiency, such as living at high latitudes [75] and vitamin D deficiency [76], have been linked to chronodisruption. Additionally, serotonin, the precursor of melatonin, was reported to adjust circadian rhythms through serotonergic afferents [77].…”
Section: Human Studies For Programming Of Adult Diseases Related To Mmentioning
confidence: 99%
“…is may be explained by their smaller muscle size, dietary difference, and bone anatomy [8]. Vitamin D deficiency also increases the risk of stress fractures [9]. In a study of 1082 Royal Marine military recruits, vitamin D deficiency below 20 μg/L has been associated with increased risk of stress fractures in military recruits [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is often misconceived that a tropical country has low rates of vitamin D deficiency. Recent studies reported that vitamin D deficiency (<20 μg/dL) was present in 13.4% of pregnant women [9] and 42% of healthy individuals [1]. In Singapore, the enrollment for compulsory national service is 18 years old which is a critical time of accruing bone mass, as peak bone mass range from early to late 20s [10].…”
Section: Discussionmentioning
confidence: 99%